Oralidade, tradição e fluidez em South-African Folk-Tales, de James A. Honey - Calderon, Elizabete Carolina Tenorio [UNIFESP] (2020)
This Master’s Degree dissertation aims at presenting a structure and thematic analysis of the narratives from South-African Folk-Tales (1910), by the South African writer James A. Honey, through a perspective which considers the African practice of orature, such as the formal elements of oral tradition. The narratives which constitute the anthology come from the oral tradition of a South African ethnic group called Khoisan. These people are characterized by a rich culture based on a long-standing oral tradition, documented since the 17th century by researchers mainly from Europe. Honey's anthology was published in a context which did not favor its original culture in all its complexity, since it was approached as an artifact representative of exotic and undeveloped cultures. By recognizing and emphasizing the fact that the piece has its core in orality, the analysis in this investigation is based on the elements of the oral text which were recognizable in the written record, following the reflections of Walter J. Ong and Isidore Okpewho. As the corpus of the research, the selection for analysis includes narratives with the presence of the trickster, a character known for his ambiguity and shrewdness in his constitution of character and way of acting. This investigation happened throughout bibliographic sources made up of authors such as Paul Zumthor and Ruth Finnegan, as well as by the theoretical foundation of African origin, especially authors as the South African philosopher Michael Wessels, the Nigerian literary critic Isidore Okpewho, the literary academic from Nigeria Amadou Hampâté Bâ and Kenyan writer Ngũgĩ Wa Thiong'o, among others.